2020
DOI: 10.3390/ma13225233
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Surface Quality, Tool Wear, and Specific Cutting Energy for Wiper and Conventional Carbide Inserts in Hard Turning of AISI 4340 Alloy Steel

Abstract: This paper presents an experimental study into the comparative response of wiper and round-nose conventional carbide inserts coated with TiCN + AL2O3 + TiN when turning an AISI 4340 steel alloy. The optimal process parameters, as identified by pre-experiments, were used for both types of inserts to determine the machined surface quality, tool wear, and specific cutting energy for different cutting lengths. The wiper inserts provided a substantial improvement in the attainable surface quality compared with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
(65 reference statements)
0
8
0
Order By: Relevance
“…Cryogenic treatment can also be used to increase the hardness of the stamps. The authors of the work in [ 4 ] showed that it is possible to increase the hardness of punches by about 2%…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cryogenic treatment can also be used to increase the hardness of the stamps. The authors of the work in [ 4 ] showed that it is possible to increase the hardness of punches by about 2%…”
Section: Resultsmentioning
confidence: 99%
“…It should be free of burrs and there should be no concentration of large plastic strains. The quality of the obtained product depends on many process parameters, such as the lubrication method, cutting speed, tool geometry, cutting clearance, punch material properties and punch wear [ 2 , 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it should be stated that hardness of materials has a significant impact for the tool life [21]. On the other hand advantages of Wiper inserts relative to conventional ones are more relevant when the cutting tool wear proceed [22]. The authors emphasize that the obtained surface roughness value is similar to that obtained in the grinding process [23,24].…”
Section: Manufacturers Of Cutting Tools Do Not Providementioning
confidence: 92%
“…In general, heat is generated during machining operation due to plastic deformation in the shear zones and friction. Consequently, high-temperature gradients are developed, resulting in tool wear [ 13 ], which, in turn, causes shattering tool failure. In order to overcome such catastrophic failures, numerous cooling techniques like flood coolant [ 14 ] and high-pressure coolant systems [ 15 ] are used during the milling process [ 16 ].…”
Section: Introductionmentioning
confidence: 99%